DIVERSITAS DAN HILANGNYA JENIS-JENIS IKAN DISUNGAI CILIWUNG DAN SUNGAI CISADANE - Hadiaty, Renny Kurnia (Research Center for Biology-Indonesian Institute of Sciences, 2011)
The fish research in Indonesian waters has been begun since 16 century ago. Most of the research collected fish around Batavia.Many new species was described and the type specimens deposited at the museums in Europe or America.The study of fish diversity and the lost of fish species was conducted at River Ciliwung and R. Cisadane in 2009. The aim of this study is to describe the recent fish diversity in both river drainages, then make a comparison with the number of species recorded based on the references data.The differences between the two datas show the number of species lost. The result of the study showed a total of 20 species of 13 families were collected in R. Ciliwung, while from the references data there were about 187 species, so the fish diversity lost in the Ciliwung river about 92.5%. The fish research in R. Cisadane were collected 39 fish species of 24 families. There were 135 species of 38 families of the references data, so the fish diversity lost in R. Cisadane is about 75.6%.